2019
DOI: 10.1371/journal.pone.0216901
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GeneXpert cycle threshold values with smear microscopy and culture as a measure of mycobacterial burden in five regional referral hospitals of Uganda- A cross-sectional study

Abstract: Background Determining mycobacterial burden is important in assessing severity of disease, evaluating infectiousness and predicting patient treatment outcomes. Mycobacterial burden assessed by smear microscopy grade and time to culture positivity is clearly interpretable by most physicians. GeneXpert (Xpert) has been recommended by WHO as a first line tuberculosis (TB) diagnostic test as an alternative to smear microscopy. Xpert gives cycle threshold (Ct) values as a potential measure for mycobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
(21 reference statements)
7
12
2
Order By: Relevance
“…The Xpert test was positive in all patients with positive smears, indicating that results of both methods correlate well. Similar results were previously reported [ 15 , 41 ], wherein comparison of the GeneXpert cycle threshold with the smear results showed that most of the "low" and "very low" Ct values in the molecular test were negative in the smear, thus proving its value in the early identification of bacilli before the culture result [ 28 ]. When compared with CRS-positive results, both AFB and culture had a similar sensitivity of 20% and 25% respectively.…”
Section: Discussionsupporting
confidence: 86%
“…The Xpert test was positive in all patients with positive smears, indicating that results of both methods correlate well. Similar results were previously reported [ 15 , 41 ], wherein comparison of the GeneXpert cycle threshold with the smear results showed that most of the "low" and "very low" Ct values in the molecular test were negative in the smear, thus proving its value in the early identification of bacilli before the culture result [ 28 ]. When compared with CRS-positive results, both AFB and culture had a similar sensitivity of 20% and 25% respectively.…”
Section: Discussionsupporting
confidence: 86%
“…This could be explained by the fact that tuberculosis is the most common opportunistic disease in HIVinfected patients. This nding has also been made by several authors (Harries et al, 2019;Najjingo et al, 2019;Phyo et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…The Xpert test was positive in all patients with positive smears, indicating that results of both methods correlate well. Similar results were previously reported [15,41], wherein comparison of the GeneXpert cycle threshold with the smear results showed that most of the "low" and "very low" Ct values in the molecular test were negative in the smear, thus proving its value in the early identification of bacilli before the culture result [28]. When compared with CRS-positive results, both AFB and culture had a similar sensitivity of 20% and 25% respectively.…”
Section: Plos Onesupporting
confidence: 85%